STRATEGI TALENT INCUBATION, MICROLEARNING, DAN SOCIAL LEARNING UNTUK MENINGKATKAN WORK READINESS DAN INNOVATIVE CAPABILITY MELALUI SELF DIRECTED LEARNING - Sari Budiarti; Sriyunia Anizar (KINDAI, 2025)
This study aims to examine the effects of Talent Incubation Strategy, Microlearning Experience, and Social Learning Support on students’ Work Readiness and Innovative Capability, with Self-Directed Learning (SDL) as a mediating variable. A quantitative approach with an explanatory survey design was employed using purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that Social Learning Support and Microlearning Experience have significant effects on SDL, while the influence of Talent Incubation Strategy is relatively weak. Furthermore, SDL has a strong effect on both Work Readiness and Innovative Capability. The R² values reveal that 55.7% of SDL variance, 41.1% of Work Readiness, and 80.4% of Innovative Capability are explained by the model. These findings highlight the critical mediating role of SDL in enhancing students’ employability and innovation capacity in digital learning environments. Keywords: talent incubation, microlearning, social learning, self directed learning, work readiness, innovative capability